Analyzing the Role of Teachers' Working Groups in Improving Teachers' Pedagogical and Professional Competencies - Musdalifah ZA; Yunus, Muh.; Syarifuddin (International Journal of Contemporary Sciences (IJCS), 2025)
This study aims to analyze the role of the Teacher Working Group (KKG) in enhancing the pedagogical and professional competence of teachers at SD Inpres Macanda, Somba Opu District, Gowa Regency. This qualitative research uses a descriptive approach with data collection techniques such as interviews, observation, and documentation. The subjects include the KKG chairperson, school principal, and teachers at SD Inpres Macanda. The findings reveal that KKG significantly contributes to improving pedagogical and professional competencies through training participation, teacher collaboration, and innovative teaching strategies. However, factors such as limited time, imbalanced participation, and irrelevant training materials present challenges. The study highlights the importance of flexible planning and tailored training to overcome these obstacles and improve the overall teaching quality.